Development of Android-Based Learning Media on Operations of Integers - Nur Afifah; Atik Wintarti (MATHEdunesa, 2023)
The ongoing digitalizing education makes the use of technology is necessary to develop the learning media. Therefore, this research describes the development process of android-based learning media with the ADDIE model and find out the validity and practicality of it. The material is operations of integers because it’s a prerequisite for many other mathematics material. The research subjects were nine 7th-grade students in SMPN 5 Jombang since they had never been given the kind of math learning media based on Android in that school. They were consist of three categories of low, medium, and high mathematical ability to determine whether all types of students can understand the presence of media to achieve their learning mastery. The data analyzed using qualitative descriptive and quantitative data analysis techniques. The result of this research and development are : 1) The Android-based learning media called Math Moist; 2) The learning media is very valid based on the results of media and material validation with a validity percentage of 83.541%; 3) The media is very practical based on the student's response questionnaire scores, with a percentage of practicality is 88.7301%; 4) Based on the result of learning outcomes test, 8 of the 9 research subjects have completed learning after using media. Keywords: development, media, android-based, ADDIE, integer.